1999
DOI: 10.1002/(sici)1521-3862(199908)5:4<143::aid-cvde143>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD-Processed Ni Films from Nickelocene. Part II: Carbon Content of the Deposits

Abstract: In this study, results are reported on the composition and the electrical and magnetic properties of thin films of nickel deposited by metal-organic CVD (MOCVD) from nickelocene. It was found that the films contain carbon, whose content decreases with increasing deposition pressure and hydrogen flow rate and with decreasing molar fraction of the precursor. Ferromagnetic properties, namely saturation magnetization, Curie temperature, and also electrical conductivity of the films decrease with increasing carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The availability of these precursors enables a wide‐range of metal and alloyed nanoparticles to be produced. A potential drawback of organometallic chemistry is the organic components which can serve as a source of contamination 39–41. This is especially true for plasma‐based processes where the energy of the electrons (or ions) are more than sufficient to break the organic bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of these precursors enables a wide‐range of metal and alloyed nanoparticles to be produced. A potential drawback of organometallic chemistry is the organic components which can serve as a source of contamination 39–41. This is especially true for plasma‐based processes where the energy of the electrons (or ions) are more than sufficient to break the organic bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] The carbon-metal bond in metallocenes is relatively more stable than that in other metalorganic compounds, making it difficult to form high quality metallic films. [13][14][15] Ruthenium films formed from (C 5 H 5 ) 2 Ru need oxygen as a reactant. [13][14][15] Ruthenium films formed from (C 5 H 5 ) 2 Ru need oxygen as a reactant.…”
Section: Introductionmentioning
confidence: 99%
“…From its very first attempt the focus of chemical vapor deposition (CVD) of nickel has been to replace the very toxic nickel tetracarbonyl, Ni(CO) 4 , with a precursor that is less toxic . Ni(cyclopentadienyl) 2 , Ni(methylcyclopentadienyl) 2 , Ni(ethylenediamine)(hexafluoroacetylacetatonate) 2 , Ni(acetylacetonate) 2 , Ni(hexafluoroacetylacetonate) 2 , and Ni(diethylglyoximate) 2 have been proposed as alternative precursors to deposit Ni with hydrogen as a reducing agent. Unfortunately, the Ni films deposited from these precursors often exhibited significant incorporation of impurities such as oxygen and carbon, even when hydrogen was employed as a reducing agent. Although it was reported that Ni(diethylglyoximate) 2 decomposed to produce pure nickel at a substrate temperature of 400 °C without H 2 , the breakdown of the ligands involved in thermal decomposition of the precursor is inherently prone to incorporating impurities in the deposited films.…”
mentioning
confidence: 99%
“…Although it was reported that Ni(diethylglyoximate) 2 decomposed to produce pure nickel at a substrate temperature of 400 °C without H 2 , the breakdown of the ligands involved in thermal decomposition of the precursor is inherently prone to incorporating impurities in the deposited films. Due to its desirable properties, the nickelocene, Ni(cyclopentadienyl) 2 , has attracted much attention; however, the Ni films deposited from it exhibited high carbon contamination, limiting its use as a CVD precursor for deposition of high-quality Ni films. …”
mentioning
confidence: 99%
See 1 more Smart Citation